2008
DOI: 10.1111/j.1556-4029.2008.00657.x
|View full text |Cite
|
Sign up to set email alerts
|

Ultraviolet Illumination as an Adjunctive Aid in Dental Inspection*

Abstract: Tooth-colored resin fillings have become increasingly popular as restorative materials. Their presence in the dentition presents a challenge to the clinician and the forensic odontologist, as detection of the fillings can be difficult both visually and radiographically. As they necessarily form part of the unique dentition of an individual, recognition of the resins is important for forensic identification. Alternative light sources have been used with success in various fields of forensic science. In recent y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
51
0
4

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(65 citation statements)
references
References 5 publications
2
51
0
4
Order By: Relevance
“…This aligns with results of previous studies analyzing composite resin materials [11,23] which showed that optimal excitation wavelengths for the composite resin materials used in their studies were in the range of 365 -380nm and 398 ± 5 nm, respectively. Fluorescence properties of materials in the mouth can be affected by the ingress of moisture as well as by degradation over time.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…This aligns with results of previous studies analyzing composite resin materials [11,23] which showed that optimal excitation wavelengths for the composite resin materials used in their studies were in the range of 365 -380nm and 398 ± 5 nm, respectively. Fluorescence properties of materials in the mouth can be affected by the ingress of moisture as well as by degradation over time.…”
Section: Discussionsupporting
confidence: 90%
“…Ultraviolet light elicits green fluorescence while blue light elicits yellow fluorescence from healthy tooth enamel. Alterations in these patterns can be used to detect missing or decalcified tooth structure (in the case of dental caries), as well as the presence of a restorative material [11][12][13]. Human enamel exhibits three distinct luminescence peaks in the regions of 350-360, 405-410 and 440-450nm [14,15].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…UV digital viewers and camcorders utilise 396nm UV-rays and can give resolution of 640 x 480 pixels. The UV-rays may be reflected or absorbed in surface layers and aid forensic medicine with detection of bitemarks and bruises 50 and the fluorescence properties identify dental materials 51 . Basal Cell Carcinomas can be recognised as dark patches and oral Squamous Cell Carcinoma may be discerned 52 .…”
Section: Ultraviolet (Uv) (Wavelength Of 10 -8 To 4 X 10 -7 M)mentioning
confidence: 99%
“…8 However, it has been documented that these materials lose their organic components and fluorescence properties after exposure to temperatures above 300°C; 9 consequently, fluorescence may not reveal restorations in cases of high temperature incineration.…”
Section: Teeth and Dnamentioning
confidence: 99%